Automated systems for access to multilingual and multiscript library materials : problems and solutions ; papers from the pre-conference held at Nihon Daigaku Kaikan Tokyo, Japan, August 21-22, 1986 - Bossmeyer, C.; Massil, Stephen W.; International Federation of Library Associations and Institutions; International Federation of Library Associations and Institutions (München ; New York : K.G. Saur, 1987)
he book included in this proceedings volume five broad subject areas- Overview of the field ,Multilingual and Multiscript applications ,advances in character sets and networking,Multilingual and Multiscript bibliographic systems and summing up.
English and Japanese.
Includes bibliographies.
Loans
Keywords: Cataloging of foreign language publications; Information storage and retrieval systems; Foreign language publications; Machine-readable bibliographic data